2016
DOI: 10.1002/1873-3468.12383
|View full text |Cite
|
Sign up to set email alerts
|

The aliphatic chain of cholesterol modulates bilayer interleaflet coupling and domain registration

Abstract: Cholesterol is a necessary component and critical regulator of liquid-ordered membrane domains. However, the structural features that determine its unique physicochemical behaviors are not fully understood. In particular, very little is known about the specific functions of the terminal aliphatic chain of cholesterol, since previous studies have focused mainly on the rigid sterol ring structure and its hydroxyl head. In the current work, we used coarse-grained molecular dynamics simulations to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…[94] Finally, the length of the acyl chain in cholesterol esters affects interleaflet coupling and domain registration. [95] In summary, the extraordinary extent of lipid asymmetry and the impact of this property on a number of complex biological and biophysical events suggest that lipid asymmetry is fine-tuned, displaying an extremely low level of tolerance to change in lipid distribution across the two halves of the bilayer.…”
Section: Membrane Asymmetry Contributes To the Biophysical Propertiesmentioning
confidence: 99%
“…[94] Finally, the length of the acyl chain in cholesterol esters affects interleaflet coupling and domain registration. [95] In summary, the extraordinary extent of lipid asymmetry and the impact of this property on a number of complex biological and biophysical events suggest that lipid asymmetry is fine-tuned, displaying an extremely low level of tolerance to change in lipid distribution across the two halves of the bilayer.…”
Section: Membrane Asymmetry Contributes To the Biophysical Propertiesmentioning
confidence: 99%
“…4c). As is known, for the phase separated lipid bilayer system, membrane domains have both the intra-leaflet [43,[45][46][47] and inter-leaflet [48][49][50][51][52][53][54] dynamics. Usually, these two kinds of membrane domain dynamics are closely related to each other.…”
Section: Lipid Nanobubble and Bi-monolayer Simulations Indicated The mentioning
confidence: 99%
“…As is discussed above, in the absence of inter-leaflet couplings, obvious membrane phase separation appears in both lipid nanobubble and bi-monolayer systems. Previous studies have indicated that inter-leaflet couplings, which can be regulated by many physicochemical factors [54] , modulate membrane domain registration/anti-registration dynamics [48][49][50] . Whether inter-leaflet couplings can affect the intra-leaflet membrane domain dynamics is still not clear.…”
Section: Lipid Bi-monolayer and Bilayer Simulations Demonstrated Intementioning
confidence: 99%
“…Notably, by shifting the free energy profiles to account for membrane thickness differences among force fields, the free energy for membrane defect formation and lipid translocation can be reconciled among different force fields [55]. For fast-diffusing steroids, such as CHL, CG MD studies found that adding fullerene [56] or increasing the length of CHL aliphatic side chain [57] significantly reduced the flip-flop rate.…”
Section: Protein-mediated Lipid Flip-flop Across the Bilayer As A Majmentioning
confidence: 99%